“Contingent power extension” and regional (dis)integration: China's Belt and Road Initiative and its consequences for the EU - Julia Gurol; Fabricio Rodríguez (Asia Europe Journal, 2022)
In this article, we explore the Belt and Road Initiative (BRI) as a case of "Contingent Power Extension" (CPE) towards the European Union (EU), assessing its implications for regional (dis)integration in the latter. CPE is a conceptual prism that interprets the BRI as a polymorphous, dynamic, and context-specific mechanism through which Chinese foreign policy elites intend to convey, amplify, and legitimize the regime's power-reach into other regions, including the EU. Along two examples—the 140.167em+0.167em1 Cooperation Forum and the Port of Genoa in Italy—we examine the power dynamics of the BRI by tracing (a) the processual impact of power extension towards the EU and (b) the (un)intended consequences for the EU in terms of (dis)integration. The findings of our analysis provide an insight into the multicausal relations between the BRI and European (dis)integration not as a static outcome but rather as a contested process of struggle. The article concludes by discussing whether and how the EU can strengthen its own institutional foundations and use its systemic leverage to respond to the BRI while enhancing regional integration in the process.
Keywords: 300; Studies in Human Society